2003
DOI: 10.1177/0013916503251473
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sensory Abilities on the Interpersonal Distance of the Elderly

Abstract: The function of sensory abilities in personal space research has been all but neglected. Elderly people experience a decline in sensory functioning as a result of the aging process or illness. Vision, hearing, and mobility were examined in relation to an elderly sample's perception of strength and aggression and established interpersonal distance. Results indicate that age, gender, and mobility play an important role in interpersonal distance. Methodological findings offer insights for future studies in person… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 20 publications
2
34
0
1
Order By: Relevance
“…This is strongly conditioned by the progressive decline in the operation of: (i) perceptive sensors (e.g., limited perception of light and colours, inability to tune out background noise) and (ii) locomotor-cognitive skills (e.g., reduced range of motion, loss of muscle strength and coordination, changes in posture, diminished attention and reaction time, spatial disorientation) [9]. All these bodily changes lead to a subjective perception of physical vulnerability and a sense of fragility at the psychological level [10].…”
Section: Age-driven Pedestrian Behaviourmentioning
confidence: 99%
“…This is strongly conditioned by the progressive decline in the operation of: (i) perceptive sensors (e.g., limited perception of light and colours, inability to tune out background noise) and (ii) locomotor-cognitive skills (e.g., reduced range of motion, loss of muscle strength and coordination, changes in posture, diminished attention and reaction time, spatial disorientation) [9]. All these bodily changes lead to a subjective perception of physical vulnerability and a sense of fragility at the psychological level [10].…”
Section: Age-driven Pedestrian Behaviourmentioning
confidence: 99%
“…It is found that there are symptoms of strong correlations between positions of closely located pedestrians [25]. The age, gender, and mobility also play important roles in interpersonal distance [26]. Compared with young people, the elderly need farther international distance [27].…”
Section: Introductionmentioning
confidence: 99%
“…One important control parameter might reside in the clearance one maintains when circumventing the obstruction. Over the last four decades, anthropologists and psychologists theorized that personal space was a zone maintained by individuals to keep others at a comfortable distance during different social interactions (Sommer, 1959;Horowitz, Duff & Stratton, 1964;Little, 1965;Hall, 1966;Dosey & Meisels, 1969;Rawdon & Willis, 1993;Webb & Weber, 2003). In the present work, the term personal space is used to describe a protective space surrounding the body during walking.…”
mentioning
confidence: 95%